Uncaria tomentosa increases growth and immune activity in Oreochromis niloticus challenged with Streptococcus agalactiae - Yunis-Aguinaga, Jefferson [UNESP]; Claudiano, Gustavo S. [UNESP]; Marcusso, Paulo F. [UNESP]; Manrique, Wilson Gómez [UNESP]; Moraes, Julieta R. Engrácia de [UNESP]; Moraes, Flávio R. de [UNESP]; Fernandes, João B. K. [UNESP] (Elsevier B. V., 2015)
Cat's claw (Uncaria tomentosa) is an Amazon herb using in native cultures in Peru. In mammals, it has been described several effects of this herb. However, this is the first report of its use on the diet of fish. The aim of this study was to determinate the effect of this plant on the growth and immune activity in Oreochromis niloticus. Nile tilapia (81.3 ± 4.5 g) were distributed into 5 groups and supplemented with 0 (non-supplement fish), 75, 150, 300, and 450 mg of U. tomentosa.kg(-1) of diet for a period of 28 days. Fish were inoculated in the swim bladder with inactivated Streptococcus agalactiae and samples were taken at 6, 24, and 48 h post inoculation (HPI). Dose dependent increases were noted in some of the evaluated times of thrombocytes and white blood cells counts (WBC) in blood and exudate, burst respiratory activity, lysozyme activity, melanomacrophage centers count (MMCs), villi length, IgM by immunohistochemistry in splenic tissue, and unexpectedly on growth parameters. However, dietary supplementation of this herb did not affect red blood cells count (RBC), hemoglobin, and there were no observed histological lesions in gills, intestine, spleen, and liver. The current results demonstrate for the first time that U. tomentosa can stimulate fish immunity and improve growth performance in Nile tilapia.
Keywords: Amazon herb; Cat's claw; Hematology; Phytotherapy